2020
DOI: 10.1186/s43141-020-00090-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening and optimization of indole-3-acetic acid production and phosphate solubilization by rhizobacterial strains isolated from Acacia cyanophylla root nodules and their effects on its plant growth

Abstract: Background Plant growth-promoting rhizobacteria (PGPR) are known to improve plant growth and are used as biofertilizers, thanks to their numerous benefits to agriculture such as phosphorus solubilization and phytohormone production. In this paper, four rhizospheric bacteria (Phyllobacterium sp., Bacillus sp., Agrobacterium sp., and Rhizobium sp.) isolated from surface-sterilized root nodules of Acacia cyanophylla were tested for their ability to solubilize inorganic phosphate and to produce indole-3-acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 59 publications
7
30
2
Order By: Relevance
“…Similarly, previous studies found that the maximum amount of IAA was produced at neutral to slightly alkaline pH [49][50][51]. Other scholars showed that the maximum yield of IAA was obtained at pH 9 [21,52]. Maximum IAA production of 81.49 μg/mL at a pH of 7…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similarly, previous studies found that the maximum amount of IAA was produced at neutral to slightly alkaline pH [49][50][51]. Other scholars showed that the maximum yield of IAA was obtained at pH 9 [21,52]. Maximum IAA production of 81.49 μg/mL at a pH of 7…”
Section: Discussionmentioning
confidence: 55%
“…Quantitative production of IAA was determined using the colorimetric method as described by Lebrazi et al [21].…”
Section: Assay For Indole-3-acetic Acid (Iaa) Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphates solubilizing microorganisms (PSM) are considered as potential bioinoculants to increase crop productivity by transforming phosphorus of the soil (the monobasic (H 2 PO 4 − ) and diabetic (HPO 4 2− ) into soluble forms assimilable by plants, through the production of organic acids, the acidification process and chelation [ 68 ]. In this study, 14 isolates were found able to solubilize tricalcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they are important in generating plant defence responses against invading pathogens [ 41 ]. IAA produced by PGPRs contribute in increasing root surface area and length, and thereby better soil nutrients uptake [ 42 , 68 ]. Interestingly, half of effective bacterial isolates produced different shades of pinkish-red, suggesting the production of this phytohormone.…”
Section: Discussionmentioning
confidence: 99%